a) $(a + b + c + d)(a + b - c - d) = ((a+b)+(c+d))((a+b)-(c+d))=(a+b)^2 - (c+d)^2=a^2+2ab+b^2 - (c^2+2cd+d^2)=a^2+2ab+b^2-c^2-2cd-d^2$
б) $(a - b + c + d)(a - b - c - d) = ((a-b)+(c+d))((a-b)-(c+d)) = (a-b)^2 - (c+d)^2=a^2-2ab+b^2-c^2-2cd-d^2$
в) $(a + b - c + d)(a + b + c - d) = ((a+b)+(d-c))((a+b)-(d-c)) = (a+b)^2 - (d-c)^2=a^2+2ab+b^2-(d^2-2cd+c^2)=a^2+2ab+b^2-d^2+2cd-c^2$
г) $(a - b - c + d)(a - b + c - d) = ((a-b)-(c-d))((a-b)+(c-d))=(a-b)^2-(c-d)^2=a^2-2ab+b^2-(c^2-2cd+d^2)=a^2-2ab+b^2-c^2+2cd-d^2$
Ответы:
a) $a^2+2ab+b^2-c^2-2cd-d^2$
б) $a^2-2ab+b^2-c^2-2cd-d^2$
в) $a^2+2ab+b^2-c^2+2cd-d^2$
г) $a^2-2ab+b^2-c^2+2cd-d^2$